22.7k views
3 votes
Find (f*f)(0)
f(x)=3x-2

Find (f*f)(0) f(x)=3x-2-example-1
User Shawanna
by
5.2k points

2 Answers

4 votes

Answer:

Choice c is correct answer.

Explanation:

We have given a function.

f(x) = 3x-2

We have to find the composition of function to itself.

(fof)(x) = ? and (fof)(0) = ?

(fof)(x) = f(f(x))

Putting values in above formula, we have

(fof)(x) = f(3x-2)

(fof)(x) = 3(3x-2)-2

(fof)(x) = 9x-6-2

(fof)(x) = 9x-8

Putting x = 0 in above equation, we have

(fof)(0) = 9(0)-8

(fof)(0) = 0-8

(fof)(0) = -8 which is the answer.

User KMLong
by
5.6k points
2 votes

Answer:

Option C. -8

Explanation:

They ask us to find

(fof)(0)

To solve this problem we must introduce the function f(x) within the function f(x)

That is, we must do g(f(x)).

So, we have:

f(x) = 3x-2

Then:

f(f(x)) = 3(3x-2)-2

This is:

f(f(x)) = 9x-6 -2

f(f(x)) = 9x-8

Now we must do x = 0

f(f(0)) = 9(0) -8

(fof)(0) = -8

The answer is: option c (fof)(0) = -8.

User Deep Sehgal
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.